Study on medium-temperature crack resistance of asphalt mastic based on filler characteristics - Haihai Zhuang (Case Studies in Construction Materials)
The road performance of asphalt is closely related to the interaction between the asphalt binder and mineral components, with asphalt mastic, a mixture of filler and asphalt, playing a key role in determining the cracking resistance of asphalt concrete. To enhance this resistance, this study investigates the influence of filler properties on the medium-temperature cracking resistance of asphalt mastic. Firstly, five types of fillers (cement, diatomaceous earth, fly ash, slaked lime, and limestone) are mixed with 70# bitumen to prepare asphalt mastic samples. The fundamental properties of these raw materials are characterized using a variety of techniques, such as scanning electron microscopy (SEM), X-ray diffraction (XRD), and specific surface area analysis. Additionally, the improved direct tensile (IDT) test is utilized to evaluate the cracking resistance of the asphalt mastic. Next, the surface energy parameters of both the asphalt and fillers are determined to examine the adhesion behavior of the asphalt-filler system. To further assess the effect of filler type and powder-to-binder ratio on medium-temperature (20 °C) cracking resistance, the IDT, double-edge notched tensile (DENT), and binder fracture energy (BFE) tests are performed. The results reveal that diatomaceous earth and slaked lime have rich surface structures, resulting in a significantly higher specific surface area than the other three fillers. As the powder-to-binder ratio increases, the cracking resistance of asphalt mastic initially improves and then declines. The optimal ratio, corresponding to the peak performance, varies with the filler type. Finally, correlations between the fracture test indices and surface energy parameters are analyzed. The results indicate a strong correlation among the indices of the BFE, DENT, and IDT tests, suggesting that all three methods are effective for evaluating the fracture performance of asphalt mastic.